Preventing theft [videorecording] - Educational Foundation (National Restaurant Association).; VTR Associates (Chicago, IL Educational Foundation of the National Restaurant Association, 1994)
Shows food service employees how to react when faced with three common types of theft: internal, customer, and external. Tells how to alert management when a co-worker is suspected of stealing and what to do when a customer leaves without paying. Explains the importance of adhering to company policies. Shows how to use care when opening and closing
VC 1941
Series title on guide: Food service security
VHS format
Keywords: Food service -- Security measures; Employee theft; Robbery; Food service employees -- Training of